Application of Response Surface Methodology for Modelling and Optimization of Hot Corrosion Rate of Nimonic 75 Coated by Ce-doped Aluminizing-Titanizing - Hussein, Abbas Khammas (Nahrain University College of Engineering Journal, 2017)
Response surface methodology (RSM) was used to determine the optimum conditions (wt.% of Na2SO4, %wt. of V2O5, and Temperature ) that give the minimum hot corrosion rate (Kp) (g2 cm-4 s-1) for Nimonic75 coated by Ce-doped Aluminizing- titanizing . Experiments were designed according to central composite design in response surface methodology with these three factors using MINITAB 16 and MATLAB 2014a Software. The variation of hot corrosion rate (Kp) with hot corrosion parameters was mathematically modeled using response surface methodology.The optimum conditions obtained were 40 wt.% of Na2SO4, 40 %wt. of V2O5, and 900oC . This resulted in ( Kp=1.430987×10-10 g2 cm-4 s-1 ) as obtained from the predicted model , which fitted well with the laboratory verification result ( Kp=1.4311×10-10 g2 cm-4 s-1 ) . This was supported by the high value of coefficient of determination (R2=99.81%) of the Predicted model . The high correlation coefficient (R2= 98.991%) between the model and the experimental data show that the model was able to predict the hot corrosion rate from hot corrosion conditions.